(untitled) (Journal of EAHIL, 2021)
Cochrane has used crowdsourcing effectively to identify health evidence since 2014. To date, over 175,000 trials have been identified for Cochrane’s Central Register of Controlled Trials via Cochrane Crowd (https://crowd.cochrane.org), Cochrane’s citizen science platform, engaging a Crowd of over 20,000 people from 166 countries. The COVID-19 pandemic presented the evidence synthesis community with the enormous challenge of keeping up with the exponential output of COVID-19 research. This case study will detail the new tasks we developed to aid the production of COVID-19 rapid reviews and supply the Cochrane COVID-19 study register. The pandemic initially looked set to disrupt the Crowd team’s plans for 2020 but has in fact served to further our understanding of the potential role crowdsourcing can play in the health evidence ecosystem.